2020
DOI: 10.1016/j.heliyon.2020.e03380
|View full text |Cite
|
Sign up to set email alerts
|

Role of high shear mixing in improving stability and bio-efficacy of botanical oil in water formulation for early stage mosquito eradication

Abstract: Neem based formulations conventionally being used as dustable powders, wettable powders, emulsifiable concentrates etc for controlling insects and mosquitoes. These formulations are prepared by mechanical mixing or low shear mixing processes. Among these formulations solvent based EC formulation is more common in use, though it have many drawbacks like phyto-toxicity, flammability, environmental contamination and dermal toxicity. Along with these drawbacks stability of the active ingredient is the most concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The neem-based oil in water emulsion formulation by high shear mixing also improves stability and bio-efficacity of the biopesticide by a decrease of particle size of the emulsion with the increase of stirring time leading to excellent emulsion stability (Iqbal et al, 2020). In addition, the stability of neem oilbased microemulsion can be enhanced by the use of botanical synergists, such as aqueous extract of Prosopis Juliflora (Sharma et al, 2019).…”
Section: Practical Problems Of Azadirachtin Applicationmentioning
confidence: 99%
“…The neem-based oil in water emulsion formulation by high shear mixing also improves stability and bio-efficacity of the biopesticide by a decrease of particle size of the emulsion with the increase of stirring time leading to excellent emulsion stability (Iqbal et al, 2020). In addition, the stability of neem oilbased microemulsion can be enhanced by the use of botanical synergists, such as aqueous extract of Prosopis Juliflora (Sharma et al, 2019).…”
Section: Practical Problems Of Azadirachtin Applicationmentioning
confidence: 99%
“…[35][36][37] The Neem oil discriminatory FTIR bands were at 2853 and 2921 cm −1 related to the alkane group with stretching vibration of C-H [38,39] and at 1742 cm −1 related to stretching ester vibration of CO. [40] Such typical bands were observed in all films containing nanoparticles with 0.5, 1, and 1.5 g of Neem oil, suggesting the success of the encapsulation and compartmentalization. To probe the overall features of the prepared films, we integrated a number of characterization techniques.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2, a decrease in mixing duration enhanced the rate of change in turbidity. Iqbal et al (2020) investigated the effect of stirring duration on droplet size and emulsion stability. They found that the turbidity change rate after 24 h decreased when a longer mixing duration was applied, which is consistent with the present study.…”
Section: Turbidity Change Ratementioning
confidence: 99%